2015
DOI: 10.1155/2015/934926
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Cell Carcinoma of the Hypopharynx: A Case Report of a Rare Tumor

Abstract: Introduction. Primary hypopharynx involvement of small cell carcinoma is very rare and very few cases have been reported in the literature. Here, we report a case of primary small cell carcinoma of the hypopharynx in a male patient. Case Report. A 50-year-old man presented with a 6-month history of sore throat and swellings in the right side of the neck. Direct laryngoscopy and biopsy revealed small cell carcinoma of the hypopharynx located in the right pyriform sinus. Discussion. Small cell carcinoma of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to previous reports, the average patient age was 64.8 years, ranging from 50 to 78 years (Table 1 ). [ 6 10 ] In the previous cases shown in Table 1 , 4 patients were male and 1 patient was female. Four patients had a history of smoking, but no patients had a history of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous reports, the average patient age was 64.8 years, ranging from 50 to 78 years (Table 1 ). [ 6 10 ] In the previous cases shown in Table 1 , 4 patients were male and 1 patient was female. Four patients had a history of smoking, but no patients had a history of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 3 patients had radiation therapy in adjunction to cisplatin-based chemotherapy. [ 6 , 7 , 10 ] Review of these 3 cases showed that 2 patients were male and that all patients had history of heavy smoking. In 2 cases, the primary tumor was found in the right pyriform sinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, current literature includes only a limited number of pure hypopharyngeal NECs. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Table 1 summarises their main characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Takagawa et al 15 presented a patient who received neck dissection and multiple courses of CRT to the primary and to lung and bone metastases, who deceased 39 months after surgery. Bayram's patient 22 had lung metastases at presentation but responded well to CRT, reported disease‐free 15 months after. Sano et al 14 achieved ‘complete response’ at primary site to CRT in a case of primary small cell carcinoma of the hypopharynx, however the patient died of lung and liver metastases 1 month after treatment.…”
Section: Discussionmentioning
confidence: 99%